What are unintended and adverse consequences?. Issue 2 (4th February 2019) - Nescolarde-Selva, Josué Antonio; Gash, Hugh; Usó-Domenech, Jose-Luis
Abstract : Purpose: The purpose of this study is to examine the unintended consequences of actions as one of the central and constituent elements of sociological theory and long debated in the history of sociology. This question has been treated under varying sociological terminologies, including, providence, social forces, social paradoxes, heterogeneity of ends, immanent causality and the principle of emergency. Design/methodology/approach: This paper is concerned with "adverse effects". The thematic contexts of "unintended consequences of social action" the authors wish to focus attention on are specific types of consequences which may merit the adjective "adverse". Findings: The analysis of the intentions of our actions and their unwanted or foreseen consequences allows us to understand how societies work. Many historical facts are probably "unintentional." But, most continuous or changing life forms must be interpreted as a mixture of intentional (social reproduction) and unintentional consequences (social change). Originality/value: This paper focuses on four points of view: the object of sociology, the problems of order and social change, the methodological status of the discipline and the nature of social explanation, and mathematical theory. Four classifications of unintended consequences are formulated from the works of Boudon, Baert and Ramos, as well as the authors.